(untitled) (UNED Research Journal, 2022)
ntroduction: Carijoa riisei (Clavulariidae) is found throughout the world in tropical waters and is considered an invasive species at certain locations. A specimen was collected intertidally in the upper Gulf of Nicoya estuary, Pacific coast of Costa Rica. The collection of the Museum of Zoology of the University of Costa Rica (MZUCR) includes additional specimens identified as C. riisei. Objective: To identify the specimen and list the MZUCR records for the Pacific coast. Methods: The coral was kept in sea water to allow observation of open polyps. The sclerites were studied under a scanning electron microscope. A list of MZUCR records was assembled. Results: The morphologies of the colony and sclerites are similar to those described for C. riisei. The MZUCR includes 50 records of C. riisei along the Pacific coast and at Coco Island. Conclusions: Based on morphology, the specimen is identified as Carijoa riisei, but genetic studies are desirable. Most of the UCRMZ records are from a decade or more ago. An evaluation of the presence of this coral in both the Pacific and Caribbean coasts is needed to better establish its present ecological role in Costa Rica.